2009
DOI: 10.1002/ejoc.200900066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lewis Acid and Solvent in the Hydrosilylation of Aldehydes and Ketones with Et3SiH; Tris(pentafluorophenyl)borane B(C6F5)3 versus Metal Triflates [M(OTf)3; M = Sc, Bi, Ga, and Al] – Mechanistic Implications

Abstract: The scope of the B(C 6 F 5 ) 3 -catalyzed hydrosilylation of (X)Ph-CH=O and (X)Ph-C(R)=O was expanded to include a large set of substitutents (X = H, , m-NO 2 , p-Et; R = Me or CF 3 ). Reactions proceed at room temperature with high chemoselectivity in a host of solvents (toluene, benzene, CCl 4 , 1,2-dichloroethane, and methylcyclohexane), or under solventless conditions, with hydrosilylation yields ranging from 85 to 95 % (for aldehydes) and 71 to 100 % (for ketones) and no noticeable solvent dependency of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 17 publications
(27 reference statements)
5
22
0
Order By: Relevance
“…It shows that in the presence of Ga(OTf) 3 , chemoselective reduction of aldimine 4 is preferred to the reduction of aldehydes 1 under the reaction conditions. A recent study by Laali et al [44] showed that formation of the corresponding benzyl ether was predominant during the Lewis acid catalyzed hydrosilylation of aldehydes and ketones using various metal triflates including Ga(OTf) 3. Therefore, we also examined the chemoselective reductive amination of functionalized benzaldehydes bearing other reducible functional groups employing the same methodology.…”
Section: Resultsmentioning
confidence: 99%
“…It shows that in the presence of Ga(OTf) 3 , chemoselective reduction of aldimine 4 is preferred to the reduction of aldehydes 1 under the reaction conditions. A recent study by Laali et al [44] showed that formation of the corresponding benzyl ether was predominant during the Lewis acid catalyzed hydrosilylation of aldehydes and ketones using various metal triflates including Ga(OTf) 3. Therefore, we also examined the chemoselective reductive amination of functionalized benzaldehydes bearing other reducible functional groups employing the same methodology.…”
Section: Resultsmentioning
confidence: 99%
“…From a sustainability point of view, the best solvent is "no solvent" but unfortunately, the reaction under solvent free condition (Table 3, entry 8) yielded only 21% of 4 d. Thus, 1,2-dichloroethane is confirmed to be the best reaction solvent for this synthetic approach. [36] To evaluate the catalyst efficiency of Yb(OTf) 3 over other possible catalysts, several metals triflate and AlCl 3 were tested under optimal reaction conditions. Stoichiometric ratio of reagents and by-products for the reductive etherification catalysed by Yb(OTf) 3 .…”
Section: Full Papermentioning
confidence: 86%
“…Although some mechanistic aspects ofthe reductive etherification of aldehydes and ketones with alkoxysilane derivatives and silaneswere reported, as proposed by Laali and Coll., [36] in our knowledge there is not mechanistic information about the direct reductive etherification of aldehydes and ketones with alcohols and silanes catalysed by Lewis acids. Although some mechanistic aspects ofthe reductive etherification of aldehydes and ketones with alkoxysilane derivatives and silaneswere reported, as proposed by Laali and Coll., [36] in our knowledge there is not mechanistic information about the direct reductive etherification of aldehydes and ketones with alcohols and silanes catalysed by Lewis acids.…”
Section: Mechanistic Hypothesismentioning
confidence: 99%
“…Aliphatic aldehydes could be applied successfully, leading to the ethers 10 and 12 in high yields ( Table 2, entries 4 and 5). [23] We also investigated the reactivities of different ketones ( Table 2, entries [6][7][8][9][10][11][12]. Surprisingly, electron-rich aromatic ketones such as acetophenone (13) showed almost no reactivity under the optimized reaction conditions ( Table 2, entry 6).…”
Section: Synthesis Of Symmetrical Ethersmentioning
confidence: 99%
“…[5] Later reports showed that a wide range of metal salts-such as BiBr 3 [5] or metal triflates [7] -were also able to activate silanes in a catalytic fashion. [8] Recently, Yadav and co-workers improved Olahs procedure by substitution of the catalyst by molecular iodine, which presumably forms the catalytically active species in situ.…”
Section: Introductionmentioning
confidence: 99%